Numerical Simulation of Particle Dynamics in a Spiral Jet Mill via Coupled CFD-DEM - Satyajeet Bhonsale; Lewis Scott; Mojtaba Ghadiri; Jan Van Impe (MDPI AG, 2021)
Spiral jet mills are ubiquitous in the pharmaceutical industry. Breakage and classification in spiral jet mills occur due to complex interactions between the fluid and the solid phases. The study of these interactions requires the use of computational fluid dynamics (CFD) for the fluid phase coupled with discrete element models (DEM) for the particle phase. In this study, we investigate particle dynamics in a 50-mm spiral jet mill through coupled CFD-DEM simulations. The simulations showed that the fluid was significantly decelerated by the presence of the particles in the milling chamber. Furthermore, we study the particle dynamics and collision statistics at two different operating conditions and three different particle loadings. As expected, the particle velocity was affected by both the particle loading and operating pressure. The particles moved slower at low pressures and high loadings. We also found that particle-particle collisions outnumbered particle-wall collisions.